1985
DOI: 10.1007/bf01309402
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol, a synthetic PGE1 analog, in the treatment of duodenal ulcers

Abstract: Misoprostol, a synthetic analog of prostaglandin E1, inhibits gastric acid production and is cytoprotective at doses well tolerated by patients in preliminary trials. This multicenter double-blind study was performed in out-patients with endoscopically demonstrated duodenal ulcers, to compare the efficacy in ulcer healing and the safety of two dosages of misoprostol and placebo. Up to six antacid tablets daily were permitted for pain. 308 patients enrolled and were randomized to three treatment groups: placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Some of them such as colloidal bismuth subcitrate and sucralfate were reported to act via stimulation of en dogenous PG biosynthesis [2,3] but others including epidermal growth factor, sulfhydryl agents, meciadanol, certain antibiotics and papaverine, were found to act via a PGindependent mechanism [4], Although it is natural that 'strengthening' of mucosal defense mechanisms by cytoprotective drugs should enhance the healing of an already established gastric or duodenal ulceration, there is no experimental evidence to support this notion. Clinical trials in hu mans with PGE analogs such as misoprostol showed that these PGs at cytoprotective doses did not enhance the healing rate of peptic ulceration [5,6]. This indicates that the mechanism of the healing effect may not be the same as the mechanism of the protec tive effect.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Some of them such as colloidal bismuth subcitrate and sucralfate were reported to act via stimulation of en dogenous PG biosynthesis [2,3] but others including epidermal growth factor, sulfhydryl agents, meciadanol, certain antibiotics and papaverine, were found to act via a PGindependent mechanism [4], Although it is natural that 'strengthening' of mucosal defense mechanisms by cytoprotective drugs should enhance the healing of an already established gastric or duodenal ulceration, there is no experimental evidence to support this notion. Clinical trials in hu mans with PGE analogs such as misoprostol showed that these PGs at cytoprotective doses did not enhance the healing rate of peptic ulceration [5,6]. This indicates that the mechanism of the healing effect may not be the same as the mechanism of the protec tive effect.…”
mentioning
confidence: 68%
“…Studies in humans showing that natural PGE may promote healing of duodenal ulcers have been taken as evidence of healing by a purely cytoprotective action [23] but this is doubtful as oral PGE2 may also exert an antisecretory activity in humans [24]. Lower nonantisecretory doses of misoprostol, found to be cytoprotective against aspirin injury [5], did not accelerate healing of gas tric or duodenal ulcerations in humans [6]. Only gastric-acid-inhibitory doses of this PGE analog showed favorable action on du odenal ulcer healing.…”
Section: Discussionmentioning
confidence: 99%
“…This non-parietal secretion may be an important component of the mucosal protective properties of prostanoids in the stomach acting to reduce the absorption of noxious substances and diluting them in bulk solution (Moody & Zalewsky, 1981;Thomson, 1984;Pihan & Szabo, 1989). Prostanoids also stimulate electrolyte secretion in the intestine (Racusen & Binder, 1980;Musch et al, 1987) that is responsible for the watery diarrhoea which has tended to limit the clinical use of prostanoids for treatment of peptic ulceration (Brand et al, 1985;Lauritsen et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In this situation mi soprostol has not been compared with the pro ton pump inhibitor omeprazole. The main side-effect of misoprostol is diarrhoea, usually mild and self-limiting, which occurs in about 13% of those taking 200 pg 4 times daily com pared to 5% of those taking placebo [7].…”
Section: Treatment Of Peptic Ulcers With Misoprostolmentioning
confidence: 99%
“…In all groups there was a significant decrease in pain during the study period but misoprostol did not differ significantly from placebo in providing pain relief. Similarly mi soprostol is more effective than placebo in healing duodenal ulcers [7].…”
Section: Treatment Of Peptic Ulcers With Misoprostolmentioning
confidence: 99%